Politik Hukum Perlindungan Sumber Daya Genetik Untuk Pemanfaatan Obat-Obatan Dalam Sistem Hukum Indonesia - Yovita Indrayati (JURNAL HUKUM, POLITIK DAN KEKUASAAN, 2021)
Predicate as one of mega biodiversity countries refers to the fact that Indonesia is a country that is rich in potential genetic resources. The genetic resources include not only plants but also animals and microorganisms. Besides meeting food needs, the genetic resources also have important benefits for the development of medicines, both traditional and modern. The medicinal benefits of genetic resources, mainly plants, have been taken advntage of the people in various regions in Indonesia. This can be seen when Covid19 pandemic hit the world, including Indonesia. the consumption of herbal medicines has increased quite sharply. Each region in Indonesia has its own type of local plants that can increase human body stamina against Covid19. The existence of the pandemic necessarily makes Indonesia more aware of the rich diversity and genetic resource’s benefits for society welfare. On the other hand, however, Indonesia faces challenges related to the biotechnology development  as well as biopiracy problems of genetic resources utilization. Therefore, protection on genetic resources is a necessity and should become an important matter for Indonesia. This paper is a conceptual study that will describe how to protect genetic resources, especially for the use of medicine, in the Indonesian legal system, which reflects the politics of law in Indonesia. Based on the results of the analysis, the commitment of The House of Representatives of the Republic of Indonesia is still weak in the formation of laws protecting genetic resources in Indonesia. However, Indonesia has a commitment to international agreements by becoming a party and ratifying the CBD, 1992; Cartagena Protocol, 2000 and Nagoya Protocol, 2011.